Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual - Sudirman, Muh.; Asis, Nurul Asmi; Nurfatirani Heri, Ririn (Jurnal Tomalebbi, 2025)
Abstract: This research aims to determine (1) The implementation of the law for children who are victims of sexual violence in the Makassar City Women's Empowerment and Child Protection Service (2) The obstacles to the Women's Empowerment and Child Protection Service in efforts to legally protect children who are victims of sexual violence. To achieve this goal, researchers used data collection techniques through interviews. The research data that has been collected and obtained is then analyzed qualitatively to determine the implementation of legal protection and the obstacles faced by the Makassar City Women's Empowerment and Child Protection Service. The results of the research show that (1) Implementation of the application of the law by the Women's Empowerment and Child Protection Service shows that significant efforts have been made in providing protection and justice for children who are victims (2) The obstacles faced by the Makassar City Women's Empowerment and Child Protection Service have several obstacles. such as from the victims themselves, obstacles in the field and also the lack of socialization or education from law enforcement officials.Keybords: Legal Protection, Sexual Violence, Children, DP3A Abstak: Penelitian in bertujuan untuk mengetahui (1) Implementasi penerapan hukum bagi anak yang menjadi korban kekerasan seksual di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Makassar (2) Kendala Dinas Pemberdayaan Perempuan dan Perlindungan Anak dalam upaya perlindungan hukum pada anak korban kekerasan seksual. Untuk mencapai tujuan tersebut maka peneliti menggunakan Teknik pengumpulan data melalui wawancara. Dari data penelitian yang telah dikumpulkan dan diperoleh kemudian dianalisis secara kualitatif untuk mengetahui Implementasi perlindungan hukum dan Kendala yang dihadapi oleh Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Makassar.Hasil penelitian menunjukkan bahwa (1) Implementasi Penerapan hukum oleh Dinas Pemberdayaan Perempuan dan Perlindungan Anak menunjukkan bahwa upaya yang signifikan dalam memberikan perlindungan dan keadilan bagi anak yang menjadi korban (2) Kendala yang dihadapi oleh Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota makassar memiliki beberapa kendala seperti dari korbannya sendiri,kendala di lapangan dan juga kurangnya sosialisasi atau edukasi dari apparat penegak hukum.Kata Kunci: Perlindungan Hukum, Kekerasan Seksual, Anak, DP3A